Pharmacokinetics and bioavailability of single dose ibuprofen and pseudoephedrine alone or in combination: a randomized three-period, cross-over trial in healthy Indian volunteers - Kale, Prashant (Frontiers in Pharmacology, 2014)
Objective To compare the bioavailability of single dose ibuprofen 200 mg and pseudoephedrine hydrochloride 30 mg administered alone or in combination as an oral suspension. Methods This was a single-center, randomized, single-dose, open-label, 3-period, crossover study. After an overnight fast (≥10 hours), 18 healthy male subjects received either ibuprofen 200 mg (reference-A), pseudoephedrine 30 mg (reference-B) or the combination (test-C) as a suspension, on 3 separate visits, with blood sampling up to 36-hours post-dose. The primary pharmacokinetic parameters, maximum plasma concentration (Cmax) and area under the plasma concentration–time curve (AUC) from time zero to last measurable concentration (AUC0-t) and extrapolated to infinity (AUC0-) were compared by an analysis of variance using log-transformed data. Bioequivalence was concluded if the 90% confidence intervals (CIs) of the adjusted geometric mean (gMean) ratios for Cmax and AUC were within the predetermined range of 80%-125%, in accordance with regulatory requirements. Results For the test formulation, the ibuprofen gMean Cmax was 17.0 µg/mL (vs. 18.1 µg/mL for reference-A), AUC0-t was 57.1 (vs. 60.0 µg•h/mL) and AUC0- was 59.9 µg•h/mL (vs. 63.1 µg•h/mL). The 90% CIs for the ratio (test/reference-A) were 81.0-108.1% for Cmax, 91.5-98.4% for AUC0-t and 91.6-97.9% for AUC0-. For pseudoephedrine, the gMean Cmax for the test formulation was 97.2 ng/mL (vs. 98.5 ng/mL for reference-B), AUC0-t was 878.4 (vs. 842.8 ng•h/mL) and AUC0- was 907.8 ng•h/mL (vs. 868.3 ng•h/mL). The 90% CIs for the ratio (test/reference-B) were 92.4-106.9% for Cmax, 97.7-111.0% for AUC0-t and 97.9-111.3% for AUC0-. All treatments were well tolerated. Conclusion This oral suspension containing ibuprofen and pseudoephedrine combined in a new formulation met the regulatory criterion for bioequivalence compared with oral suspensions containing the individual components.